The impact of e-governance on the performance of employees in government institutions: a field study at the Ministry of Finance in the Government of National Unity (Comprehensive Journal of Science, 2025)
The aime of This study is to identify the affect of E go earn e Witt lits dimensions (E administration E Transparency E accountability Sharing and E auditory) on the performance of employées in the Ministry of Finance in the National Unity Gouvernement.  The study used the Corrélationnel Descriptive Research and quantitive research. A questionnaire Waas used to collect data. The semple was chose randomly winch us 267 employèes.the data was analyzed and test using SPSS programme.The results were That There is a positive résulte Witt (0.05) for E gouvernance with all its dimensions of the performance e of employées in the Ministry of Finance.  Also the level ofApplying the E gouvernance Wit in the Ministry of Finance was medium